2001
DOI: 10.1103/physrevb.64.115116
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission and band-calculation studies of the charge-density wave inCuV2S4

Abstract: We have studied the electronic structure and its changes across the charge-density-wave ͑CDW͒ transition in spinel-type CuV 2 S 4 by photoemission spectroscopy and first-principles band-structure calculations. The photoemission spectra show pseudogap-like behavior and the gap size is estimated to be ϳ90 meV. The large energy scale of the pseudogap compared to the transition temperature and its anomalous temperature dependence implies that the involved interaction is in the strong-coupling regime. The calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…12 from that reported in [1,3,4,6]. The latter data had a sharp decrease at 90 K. The sin- gle crystal and the fine powders used in the present investigations were grown by Nagata's group, who already reported the important magnetic, electric, and thermal properties of CuV 2 S 4 [7,8,10,11,15,16]. At the moment, it is not easy for us to explain the origin of the difference, though we think that the results depend on the type of specimen used -one single crystal, single crystals, polycrystalline fine powders, and polycrystals -in addition to the instrumental condition of the measurements, because the susceptibility depends on correlation between the crystallographic orientation of the specimen used and the direction and strength of the applied magnetic field.…”
Section: (C)supporting
confidence: 51%
See 2 more Smart Citations
“…12 from that reported in [1,3,4,6]. The latter data had a sharp decrease at 90 K. The sin- gle crystal and the fine powders used in the present investigations were grown by Nagata's group, who already reported the important magnetic, electric, and thermal properties of CuV 2 S 4 [7,8,10,11,15,16]. At the moment, it is not easy for us to explain the origin of the difference, though we think that the results depend on the type of specimen used -one single crystal, single crystals, polycrystalline fine powders, and polycrystals -in addition to the instrumental condition of the measurements, because the susceptibility depends on correlation between the crystallographic orientation of the specimen used and the direction and strength of the applied magnetic field.…”
Section: (C)supporting
confidence: 51%
“…The crystals were synthesized from the powders in a quartz ampoule by TeCl 4 vapor transport at a growth temperature of 830 °C to 720 °C in a two-zone furnace [16]. The size of the single crystal used, but not twinned, had a rectangular shape of about 1.8 × 2.8 × 3.7 mm…”
Section: Experimental and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoemission spectroscopy is a standard tool to identify the CDW state. 30,31 However, in a previously published photoemission study on Ni 2 MnGa, the existence of CDW was not established, although a temperature dependent variation of the spectral shape near E F in the pre-martensite phase was observed, it was related to the density of states (DOS) in the martensite phase.…”
mentioning
confidence: 94%
“…The spectral weight transfer from below E F to higher BE was predicted by theory of CDW 3 that considers the electron-phonon coupling. Furthermore, from the photoemission studies on other CDW systems, 30,31,50 the spectral weight transfer has been reported to occur over an energy range much larger than the pseudogap. This is also observed here: the spectral weight transfer occurs over the energy range of 0.25 to 0.85 eV (Fig.…”
Section: 57mentioning
confidence: 99%